Strategi Pengembangan Objek Wisata Pemandian Lombongo Kabupaten Bone Bolango - Nur Djali, Sri Novita Afriani; Nani, Yacob Noho; Tohopi, Rustam (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to identify and describe the development strategy for the Lombongo baths as a tourism object, as well as to identify the government’s startegy for developing Lombongo tourism through the aspects of strenghts, weaknesses, opportunities, and threats. The research method is descriptive qualitative, and the data collection technique is through observation, interviews, and documentation. The data analysis uses the Huberman method. The findings show that several aspects of the development startegy for the Lombongo baths as a tourism object in Bone Bolango Regency is conducted optimally. For Example, from the strenghts aspect, it is identified that the infrastructure facilities for this tourism object are already optimized, and from the opportunities espect, it is identified that the development of this tourism object is well conducted as it can help the local community. However, several aspects are not well optimized, such as in the weaknesses aspect, it is identified that some units that are built by the local government have not functioned optimally due to the lack of custodians for each unit, and in the threat aspect is the probability of natural disasters that can cause significant losses.